Development of a templating program for data management automation - Gulnara A. Gareeva; Aigul G. Faizullina; Asiya A. Mirsaitova; Sh. Zulfina Aglyamova; Nuriya R. Zakirova (International Journal of Advanced Studies)
Background. Integrated development environments, have limited ability to automate repetitive tasks, which leads to increased development time. Creating a software templating tool solves this problem by automating routine processes and reducing errors.